{Isolation, Characterization, and Independent Synthesis of Guanine Oxidation Products} - Gimisis, Thanasis; Cismas, C; Cismaş, Crina (European J. Org. Chem., 2006)
Oxidatively produced DNA damage is a physiological process that has been associated with many human conditions. Of the four DNA bases, guanine is the most easily oxidized and exhibits a large number of oxidation products. The focus of this Microreview is on the structure of the proposed intermediates and final products of guanine oxidation, as determined by spectroscopic methods and independent synthetic studies. The major and minor primary and secondary oxidative DNA lesions that arise from the oxidation of guanine under a variety of conditions, as well as associated structures, are described and all the relevant information regarding the isolation, characterization, and independent synthesis or generation of these lesions in synthetic oligonucleotides is presented. Finally, information on the biological studies that have been advanced, based on the basic molecular information obtained by the aforementioned studies, is provided. © Wiley-VCH Verlag GmbH {&} Co. KGaA, 2006.
Keywords: DNA damage; Guanine; Nucleo; [Bioorganic chemistry